2020
DOI: 10.3390/agronomy10020290
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Storage and the Stratification Ratio of Soil Organic Carbon under Different Vegetation Types in Northeastern China

Abstract: The depth distribution of soil organic carbon (SOC) in a soil profile is important to examine the effects of different treatments on SOC sequestration. This study was conducted to determine the effects of different vegetation types on the concentration, storage, and stratification ratio (SR) of SOC in northeastern China. Five vegetation types, Leymus chinensis (LEY), Puccinellia tenuiflora (PUC), Echinochloa phyllopogon (ECH), saline seepweed (SUA), and Chloris virgata Swartz (CHL), were selected as treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…In the deep soil of the 60-80 and 80-100 cm layers, the SOC content in NT soil was significantly lower than that in CT soil. Yu et al, (2020) also found that the greater SOCS was observed in the LEY treatment as compared to PUC ≈ ECH > CHL > SUA treatments at 0-10 cm depth. At the 10-20 cm depth, SOCS in the LEY, PUC and ECH treatments was significantly higher than that in the SUA and CHL treatments.…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…In the deep soil of the 60-80 and 80-100 cm layers, the SOC content in NT soil was significantly lower than that in CT soil. Yu et al, (2020) also found that the greater SOCS was observed in the LEY treatment as compared to PUC ≈ ECH > CHL > SUA treatments at 0-10 cm depth. At the 10-20 cm depth, SOCS in the LEY, PUC and ECH treatments was significantly higher than that in the SUA and CHL treatments.…”
Section: Introductionmentioning
confidence: 67%
“…At 5-10 and 10-15 cm soil depths, the SOC concentrations under RT-RWMB varied significantly from other treatments. Yu et al, (2020) reported that -10 cm depth and the lowest value (1.370 g kg −1 ) in the SUA treatment at the 40-50 cm depth. The range of the SOC concentrations across the soil profile was 10.970, 7.230, 6.937, 4.408, and 6.025 g kg −1 for the LEY, PUC, ECH, SUA, and CHL treatments, respectively.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Changes in the reserves of elements of the mineral nutrition of plants can lead to a decrease in the adaptive potential of the phytocenosis and deterioration of the forest-growing properties of soils [23,24]. Differentiation of the soil profile into separate horizons determines the specifics of their properties (for example, the stocks of carbon, nitrogen and potassium), and this is a common phenomenon in many natural ecosystems [25]. In this regard, it is possible to use a very informative indicator (soil stratification coefficient) that may change against the background of anthropogenic impact.…”
Section: Introductionmentioning
confidence: 99%
“…The soils of degraded grasslands have a very high potential for carbon sequestration (i.e. removing CO2 from the atmosphere and storing it in the soil via meadow sward) [11].…”
Section: Introductionmentioning
confidence: 99%